2008
DOI: 10.1590/s0104-56872008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da terapia para desvios fonológicos com diferentes modelos terapêuticos

Abstract: the results indicate that the three therapy approaches were effective in the treatment of children with PD, and were effective in treating different severity levels. Besides that, most of the changes occurred in the phonological system of the groups with more severe PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 13 publications
9
25
0
20
Order By: Relevance
“…Other studies also reported the acquisition of sounds in the phonetic inventory after the therapy from different intervention phonological models [14][15][16]25 . According to the literature 10,30 , the use of a computer, as an intervention instrument is capable of favoring better results in relation to the development in the phonological system when compared to the standard therapy, since the specific software is a way to innovate the speech therapy in order to make it more appropriate to current interests of the child 10,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies also reported the acquisition of sounds in the phonetic inventory after the therapy from different intervention phonological models [14][15][16]25 . According to the literature 10,30 , the use of a computer, as an intervention instrument is capable of favoring better results in relation to the development in the phonological system when compared to the standard therapy, since the specific software is a way to innovate the speech therapy in order to make it more appropriate to current interests of the child 10,29 .…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were submitted to speech and hearing screening which included a speech and language assessment, in order to identify children with phonological disorders. The speech assessment was performed from spontaneous naming through thematic figures, used in other studies [8][9][10][13][14][15][16][17] .…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they mention differences regarding the treatment duration, in the phonemes acquisition or in the increase of the Percentage of Correct Consonants (PCC) in cases of phonological disorder, some studies (7)(8)(9)(10) observe that the different models are efficient to treat the different severities of the phonological disorder. Besides, they reveal the importance of the speech language therapy, with phonological basis to the adjustment of the speech pattern of children with phonological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In general, researches in the area (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) aimed at describing the improvements obtained through the treatment. However, it is important to understand the course of acquisition in which, even without therapy, the child with phonological disorder goes through with the purpose of supplying, or not, their speech difficulties as time passes, evidencing that the changes in the phonological systems, which are stagnant, may occur, without therapy.…”
Section: Introductionmentioning
confidence: 99%